The Boys in the Band Based on a Play by Mart Crowley - Crowley, Mart (Second Sight, 2019)
Premiering Off-Broadway in April 1968, Mart Crowley's groundbreaking play "The Boys in the Band" was a hit with queer and straight theatregoers alike. Two years later it was adapted for the screen by Crowley, and upon the playwright's insistence the William Friedkin directed movie featured the entire cast from the original stage production. Initially hailed by the queer community for its rare representation of gay men in mainstream culture, over the years as gay liberation gained momentum, "The Boys in the Band" became viewed by many as a potential hindrance to acceptance. It was feared that the characters portrayed a negative image of gay life that reinforced stereotypes; a shadow that loomed over the work for some decades. An unfair burden on any piece of entertainment or artwork featuring underrepresented groups that's seen resistance or immediate backlash to the likes of Friedkin's "Cruising" in 1980 and Russel T. Davies' television series "Queer as Folk" in 1999. Although a mainstream film featuring more or less an entire cast of LGBTQ characters, such as "The Boys in the Band", is still a relative rarity, thankfully representation and societal acceptance has shifted to a degree that allows further richness and complexity, and perceived negative traits in gay characters, without concerns that the entire community will be judged. [thequeerreview.com]
Keywords: Blu-Ray-Disc